The risk of sarcopenia 24 months after bariatric surgery - assessment by dual energy X-ray absorptiometry (DEXA): a prospective study - Pekař, Matej; Pekařová, Anna; Bužga, Marek; Holéczy, Pavol; Soltes, Marek (Wideochirurgia i inne techniki maloinwazyjne, 2020)
INTRODUCTION: Bariatric procedures lead to changes in body composition. Desired fat loss may be accompanied by decrease of muscle mass, thus raising the risk of sarcopenia. AIM: To detect the risk of sarcopenia in patients 24 months after different bariatric/metabolic (B/M) procedures by DEXA. MATERIAL AND METHODS: Consecutive patients scheduled for a B/M procedure underwent DEXA scan and anthropometric assessment before and 24 months after surgery in a prospective manner. Obtained data were tested for significant differences (p < 0.05) to detect body composition changes and occurrence of sarcopenia. The International Physical Activity Questionnaire (IPAQ) was answered at 24 months to assess physical activity. RESULTS: Nineteen patients were enrolled, with no drop-off at follow-up. Body mass index dropped from 42.4 ±6.3 to 30.3 ±4.9 kg/m2, with excess weight loss of 72 ±25% and substantial improvement of all relevant anthropometric measurements (p < 0.001). Significant changes in DEXA parameters were observed: fat mass index (19.5 ±4.7 vs. 12.1 ±3.7 kg/m2), estimated visceral adipose area (235.8 ±70.0 vs. 126.5 ±50.4 cm2), lean mass index (22.1 ±2.4 vs. 18.1 ±2.3 kg/m2), appendage lean mass index (9.7 ±1.3 vs. 7.7 ±1.1 kg/m2), bone mineral content (1.22 ±0.1 vs. 1.12 ±0.1 kg), Z score (2.32 vs. 0.96) and T score (0.58 vs. -0.58). A low level of physical activity was recorded at 24 months. CONCLUSIONS: B/M procedures lead to significant changes in body composition at 24 months after surgery. DEXA detects these changes effectively. Desired fat loss is associated with significant reduction of skeletal muscle and bone mineral mass. As such, patients after B/M surgery are at risk of sarcopenia. A low level of physical activity may also play a negative role.
Keywords: sarcopenia; bariatric surgery; dual-energy X-ray absorptiometry; obesity; laparoscopy; metabolic surgery